1968
DOI: 10.1002/bbpc.19680720917
|View full text |Cite
|
Sign up to set email alerts
|

Elektronenspektren und Elektronenstruktur von 9,9'‐Dianthryl

Abstract: Abstract9,9'‐Dianthryl zeigt eine Verschiebung und Strukturänderung seiner Fluoreszenzbande in Abhängigkeit von der Polarität und Viskosität des Lösungsmittels, die für einen derartigen Kohlenwasserstoff anomal ist. Dieses Verhalten kann durch die Annahme eines intramolekularen Ladungsüberganges und einer Verdrillung im angeregten Zustand erklärt werden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Symmetry breaking charge transfer (SBCT) in excited dimers and symmetric donor-acceptor chromophoric aggregates has been studied for several decades with increasing intensity. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] This process is considered a promising tool for efficient charge separation and energy conversion in organic electronics 15,16 as well as in biological systems. 17,18 This is due to the fact that it occurs in an activationless regime 19 and, therefore, very quickly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Symmetry breaking charge transfer (SBCT) in excited dimers and symmetric donor-acceptor chromophoric aggregates has been studied for several decades with increasing intensity. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] This process is considered a promising tool for efficient charge separation and energy conversion in organic electronics 15,16 as well as in biological systems. 17,18 This is due to the fact that it occurs in an activationless regime 19 and, therefore, very quickly.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30] The experimental study of SBCT has begun with bianthryl, a symmetric dyad. 1 It has been shown that the interaction of the appearing dipole moment of a molecule with a polar medium can stabilize the state with separated charges. 31 A detailed experimental and theoretical exploration of SBCT in 9,9 ′ -bianthracene was fulfilled.…”
Section: Introductionmentioning
confidence: 99%
“…[5] The CT nature of BA was initially discerned from the positive solvatochromism evident in its steady-state fluorescence spectra. [18,19] Subsequently, a diverse array of time-resolved spectroscopic techniques, including time-resolved absorption, fluorescence, vibrational, and microwave conductivity spectroscopies, has been employed to elucidate the underlying mechanisms governing SB-CT in BA. [20][21][22][23][24][25][26][27][28][29] These experimental approaches collectively proposed that the pivotal factors enabling the formation and stabilization of the CT state in BA are the torsional motion along the CÀ C bond connecting the two anthracene (An) chromophores and the fluctuations of solvation shells.…”
Section: Introductionmentioning
confidence: 99%